Marketing Strategy Analysis, Product Effectiveness, and Services of Bank Syariah Indonesia in Enhancing Competitiveness in Jambi City - Ary Dean Amri; Dinda Angelina Ismanto; Arnes Sopia; Muhammad Imam Ghazali; Rizki Anggraini (MALIA: Jurnal Ekonomi Islam, 2023)
This study aims to analyze the extent to which marketing strategy and the effectiveness of products and services contribute to enhancing the competitiveness of Bank Syariah Indonesia. The research method employed in this study is quantitative research. The research subjects are productive individuals in Jambi City, with a total of 100 respondents. Based on the results of the T-test and F-test for the variables (X1) marketing strategy and (X2) effectiveness of products and services, a significant value of 0.000 < 0.005 was obtained. Therefore, it can be concluded that both the marketing strategy (X1) and the effectiveness of products and services (X2) jointly influence the competitiveness of Bank Syariah Indonesia. The results of the adjusted R2 test in this study yielded an adjusted R2 value of 0.723. This indicates that in enhancing the competitiveness of Bank Syariah Indonesia, marketing strategy, product effectiveness, and services account for 72.3% of the influence, while the remaining 27.7% is influenced by other factors not examined in this study.